THE ANALYSIS OF THE CONTENT OF DAKWAH MESSAGES IN THE BOOK: UDAH PUTUSIN AJA! WRITTEN BY FELIX Y. SIAUW - Pina Purnama Lubis; Mutiawati Mutiawati (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2022)
The purpose of this study was to find out what da'wah messages were conveyed by Ustadz Felix Y. Siauw in the book Udah Putusin Aja!, both in aqidah messages, moral messages, and shari'ah messages. The researcher also finds out which message is more dominant in this book so that the researcher can conclude what the contents of this thesis are. The method used in this research is the library method in the form of content analysis. In collecting data, Library Research technique is used with Cooding Sheet technique. Then the technique used in analyzing is descriptive analysis which describes in detail what problems are discussed. The research findings show the messages of da'wah (3 aqidah messages, 7 morals and 18 shari'ah messages) in the book Just Break Up! this is a message not to do an act that is very clearly unlawful, namely dating. Many da'wah messages can be taken from this book, including messages not to commit adultery, to do ta'aruf properly and correctly, and many more da'wah messages that can be applied in everyday life. The results also show that messages about aqidah and sharia are more dominant in the book under study.